Implementasi Algoritma C4.5 untuk Klasifikasi Status Tingkat Pengangguran di Indonesia Berdasarkan Jenjang Pendidikan: Penelitian - Fadel Tri Ismar; Muhammad Reza; Muhammad Faizal Afif; Muhammad Rayyan Saputra; Ammar Ammar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Unemployment is one of the main economic problems in Indonesia that fluctuates every year. Data from the Central Statistics Agency (BPS) shows that the level of education does not always guarantee the absorption of the workforce, where the phenomenon of educated unemployment (vocational high school/university graduates) often occurs. This study aims to classify the status of the national unemployment rate (category